Методика виявлення фенів-маркерів елементарних популяцій Drosophila melanogaster Mg на техногенно трансформованих територіях - Руденко, С.С.; Легета, У.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The scheme of revealing the pheno-markers among the morphological and qualitative attributes for elementary populations Drosophila melanogaster Mg. on technotransformed territories is offered and tested.